An Update on Psychoactive Substances: Pharmacology and Toxicology Issues - Stefania Chiappini; Fabrizio Schifano (MDPI AG, 2023)
This Special Issue, titled "Psychoactive Substances: Pharmacology and Toxicology", aims to provide an up-to-date overview of the pharmacology, clinical information, and toxicology of psychotropics, as well as the effects associated with their intake [...]